Negotiating to Avoid Gradual versus Dangerous Climate Change: An Experimental Test of Two Prisoners' Dilemma - Scott Barrett; Astrid Dannenberg (Center for Economic Studies and ifo Institute (CESifo), 2014)
According to the Framework Convention on Climate Change, global collective action is needed to stabilize “greenhouse gas concentrations in the atmosphere at a level that would prevent dangerous [our emphasis] anthropogenic interference with the climate system.” The Framework Convention thus implies that, on the far side of some critical concentration level, climate change will be “dangerous,” while on the near side of the threshold, climate change will be “safe” (though perhaps still undesirable). Rather than be linear and smooth, the Framework Convention warns that climate change may be “abrupt and catastrophic.”
Keywords: C72; F51; H41; H87; Q54; 330; climate change; prisoners' dilemma; catastrophe; negotiations; cooperation; uncertainty; experimental economics